2023
DOI: 10.20944/preprints202303.0071.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Memories of COVID-19: The Types of Fitted Face Masks Between Public Health Advice and Personal Choice

Abstract: As the COVID-19 pandemic begins to abate and national public health systems are treating the SARS-Cov-2 virus as endemic, many public health measures are no longer mandated, but remain recommended with voluntary participation. One of these is the wearing of fitted face masks, initially mandated to contain, or at least slow, the spread of SARS-CoV-2 which is primarily transmitted via aerosols emitted while breathing, coughing, or sneezing. While the habit of once wearing fitted face masks recedes into memory fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…All fitted face masks discussed in this paper were encountered by the author between March 2020 and December 2022 in Albury, a major regional city in southern New South Wales, Australia. This study is based on a total of 3652 different masks which were observed as being worn, lost, discarded, or donated [13,14,[44][45][46][47]. The location can be regarded as representative of communities along the eastern seaboard of Australia as there are no significant differences in mask usage between Albury and the metropolitan centers of Sydney or Melbourne [48,49].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All fitted face masks discussed in this paper were encountered by the author between March 2020 and December 2022 in Albury, a major regional city in southern New South Wales, Australia. This study is based on a total of 3652 different masks which were observed as being worn, lost, discarded, or donated [13,14,[44][45][46][47]. The location can be regarded as representative of communities along the eastern seaboard of Australia as there are no significant differences in mask usage between Albury and the metropolitan centers of Sydney or Melbourne [48,49].…”
Section: Methodsmentioning
confidence: 99%
“…Soon after the shortage of surgical-type face masks had become evident, public health departments published design instructions for simple masks, [66] while national drapery chains offered sewing templates [67,68]. A wide range of mask types was produced with both pleated (Figures 1 and 27) and one-piece designs (Figure 2) both with (Figure 28) and without nose wires (Figures 29 and 30) [13]. Some artisanal designs even included removable filter layers.…”
Section: Fabric Masks Artisanal Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2020 and 2023, the author systematically photographed, collected and documented examples of material culture associated with the COVID-19 pandemic in Albury, a major regional service centre in southern New South Wales (NSW) at the border to Victoria (Australia) [46,50,[73][74][75][76]. This is the only systematic and comprehensive documentation of its kind in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…This shortage was exacerbated by hoarding and panic buying [9]. In consequence, a cottage industry sprung up to manufacture face masks made from cotton and other cloth fabric [10,11], which, while better than no mask at all, provided a lower level of protection from SARS-CoV-2 compared to N95 or single-use surgical-type face masks.…”
Section: Introductionmentioning
confidence: 99%